Low Self-Control, Peer Delinquency, and Crime: Considering Gendered Pathways. (November 2021) - Stults, Brian J.; Hernandez, Jorge Luis; Hay, Carter
Objectives: We extend prior research by considering how low self-control and peer delinquency may work together in a mediating process whereby low self-control increases association with delinquent peers, which in turn increases criminal offending. Further, we draw on gender crime research to suggest that the indirect effect of self-control on offending will be greater for boys than girls. Methods: We use three waves of data from the Project on Human Development in Chicago Neighborhoods to test these hypotheses for violent offending, property offending, and substance use, using multi-group multilevel generalized structural equation models that address issues of time ordering, spuriousness, and the measurement of criminality. Results: The hypothesized mediation process is supported by our results. We also find that the indirect effect of low self-control on violence and property crime is greater for boys, primarily driven by a stronger effect of delinquent peers for boys. In contrast, and in support of expectations, the results for substance use reveal little gender difference. Conclusions: We conclude that rather than treating self-control and peer delinquency as competing explanations, we should view them as working together to affect crime and delinquency. Moreover, researchers must give careful attention to gender differences in the pathways to offending.